Understanding corporate annual reports : - Stanko, Brian (John Wiley & Sons, 2003)
Understanding Corporate Annual Reports: A User’s Guide is a very valuable tool in helping to read between the lines and build a better understanding of all the details contained in an annual report. It is written using layman’s terms and anecdotal evidence that make it easy for the average investor to follow. This book will certainly help me become a more knowledgeable and informed investor in the future